Evaluasi Pembangunan Infrastruktur Jaringan Irigasi di Kabupaten Bengkulu Tengah - Rahmat Al Hidayat (UNIVED Press, 2022)
This study aims to determine the extent of success of the program being implemented, so that from this evaluation new ideas can be found in the planning of the next program. It can be said that the evaluation is used as a working reference for more optimal infrastructure development. The results of the questionnaire assessment showed that the application of irrigation network infrastructure development in Bengkulu Tengah Regency was strongly supported by farmer groups, which was carried out in the Likert Scale calculation, by finding the percentage value of the average score interpretation criteria in figures of 81% to 100% percentage listed very strong. Based on the results of the study using the reliability test calculation with the help of SPSS software, the Cronbach alpha value obtained with the implementation variable was 0.838, and the utilization was 0.768, it turned out to have a Cronbach's Alpha value greater than 0.70, which means both variables were declared reliable or fulfilled the requirements.